2020
DOI: 10.1177/0973217920928645
|View full text |Cite
|
Sign up to set email alerts
|

Successful Use of Propranolol in a Symptomatic Giant Congenital Hepatic Hemangioma

Abstract: Congenital hepatic hemangiomas are rare benign vascular tumors present at birth. They often are asymptomatic but can have significant complications and mortality that directly correlate with the tumor characteristics and size. Congenital hemangiomas generally regress during the first year of life and are managed medically or surgically depending on its course. We present a case of a full-term newborn with a symptomatic giant congenital hepatic hemangioma that received propranolol and corticosteroid therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Results from previous studies revealed mixed results in cases of medically-treated CH including partial, complete, or in some cases, no improvement at all ( 17 21 ). As most CHs ultimately involute, the positive outcomes reported may not all be attributed to the effects of medication ( 22 ). Our experience with a single case revealed that although propranolol improves cardiac function, it does not promote significant involution of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Results from previous studies revealed mixed results in cases of medically-treated CH including partial, complete, or in some cases, no improvement at all ( 17 21 ). As most CHs ultimately involute, the positive outcomes reported may not all be attributed to the effects of medication ( 22 ). Our experience with a single case revealed that although propranolol improves cardiac function, it does not promote significant involution of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…For focal HH that is mostly assumed to be CHH, drug treatment is not recommended; in cases of shunting with high flow and high output cardiac failure, embolization [ 3 ], or alternatively steroid treatment or surgical excision is proposed [ 4 6 7 ]. Considering the successful management of focal HH with propranolol reported in the literature [ 8 9 10 11 12 13 ], we believe that the current treatment recommendations for focal HH should be redefined.…”
Section: Introductionmentioning
confidence: 99%